Gambaran Tenaga Kefarmasian Dalam Memberikan Informasi Kepada Pelaku Swamedikasi di Apotek-Apotek Kecamatan Tampan, Pekanbaru - Septi Muharni; Fina Aryani; Maysharah Mizanni (Jurnal Sains Farmasi & Klinis, 2015)
The performance of all pharmacist staff including pharmacist, pharmacist assistance and pharmacist technician in drug information service towards self medication patient affect the therapeutic success. Self medication is the way of therapy with drug medication which drugs can be obtained at pharmacy without needing doctor’s prescription. The research aims to evaluate the description of drug information service given by all pharmacist staff on self medication of tooth pain patient at the pharmacy located around Kecamatan Tampan, Pekanbaru. It was conducted using cross sectional planning survey by participative observational method. 30 pharmacist staffs who give mefenamic acid as tooth pain drug were selected as respondent. The assessment was done using Likert scale. The result showed that drug information service given by all pharmacist staffs was in good scale (63.10%) and still conducting passively or they gave drug information if only the patient asked. The detail result demonstrated that 63.20% of pharmacist afforded adequate scale of drug information service, the pharmacist assistant gave 60% of adequate scale, while the pharmacist technician exhibited 63.80% good scale. The route of drug usage was the most common information with very good category (85.33%).